Implikasi Infak, Sedekah, dan Wakaf terhadap Perekonomian - Zikry Ramadhan; Farhan Fadlirahman (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This research entitled “ISWAF Implications For The Economy” aims to analyze the benefits of infaq, sadaqah, and waqf Indonesia’s economic development. This research uses descriptive method and uses secondary data derived from journal literature related to the research title. The result of this study indicate that ISWAF has enormous potential for the development of the Indonesia’s economy.